Scrapbook Media Improves Fifth Grade Science Learning Outcomes: Media Scrapbook Meningkatkan Hasil Pembelajaran Ilmu Pengetahuan Alam Kelas Lima - Nuha, Fanina Ulin; Wulandari, Fitria Eka (Indonesian Journal of Education Methods Development, 2026)
This study examines the use of scrapbook media in elementary science learning. General Background: Science education in elementary school emphasizes cognitive development based on Bloom’s taxonomy to support students’ understanding of natural phenomena. Specific Background: In grade V at SD Muhammadiyah 1 Waru, student learning outcomes in the topic of the human respiratory system were below the minimum mastery criteria due to teacher-centered instruction and limited learning media. Knowledge Gap: Although previous studies have discussed scrapbook media, limited evidence is available regarding its application to cognitive indicators C1–C4 in elementary science contexts using N-Gain analysis. Aims: This research aims to determine the effect of scrapbook media on students’ cognitive learning outcomes. Results: Using a quantitative pre-experimental One Group Pretest-Posttest Design with 27 students, the mean pretest score was 60.8 and increased to 88.9 in the posttest, with an N-Gain score of 0.71 categorized as high. Improvements were observed across remembering, understanding, applying, and analyzing indicators. Novelty: The study provides structured cognitive indicator analysis of scrapbook-based instruction in the human respiratory system topic. Implications: Scrapbook media supports meaningful science learning and can be utilized as an alternative instructional medium in elementary classrooms. Keywords: Science Learning, Scrapbook Media, Cognitive Learning Outcomes, Elementary Education, N-Gain Analysis Key Findings Highlights Post-instruction scores showed a substantial increase compared to baseline results. Remembering and understanding indicators reached high gain categories. Applying and analyzing skills demonstrated moderate improvement trends.